A framework for travel time variability analysis using urban traffic incident data. (April 2018) - J. Javid, Roxana; Jahanbakhsh Javid, Ramina
Abstract: This study aims to develop a framework to estimate travel time variability caused by traffic incidents using integrated traffic, road geometry, incident, and weather data. We develop a series of robust regression models based on the data from a stretch in California's highway system during a two-year period. The models estimate highway clearance time and percent changes in speed for both downstream and upstream sections of the incident bottleneck. The results indicate that highway shoulder and lane width factor adversely impact downstream highway clearance time. Next, travel time variability is estimated based on the proposed speed change models. The results of the split-sample validation show the effectiveness of the proposed models in estimating the travel time variability. Application of the model is examined using a micro-simulation, which demonstrates that equipping travelers with the estimated travel time variability in case of an incident can improve the total travel time by almost 60%. The contribution of this research is to bring several datasets together, which can be advantageous to Traffic Incident Management. Highlights: Highway clearance time is estimated using weather, road geometry, and incident data. Travel time variability under incident condition is estimated fairly accurately. Travel time is decreased by 60% if travel time variability is provided to drivers. The results can be used by Traffic Incident Management to improve mobility.